Knowledge Level of Beneficiaries of CSSDM-Vocational Training Programme: Comparative Analysis Across Selected Course Groups (Indian Journal of Extension Education, 2024)
Regular education and comprehension enhance knowledge, which opens doors to career options. Thus, the study focused on the Chhattisgarh State Skill Development Mission (CSSDM), which has been in place since 2009 and aims to enhance recipients’ knowledge, abilities, and attitudes to create possibilities for meaningful work. With 250 beneficiaries, the study was carried out in 2021 in the Bilaspur District of Chhattisgarh to meaningfully determine the factors that influence the patterns of knowledge acquisition among different beneficiary subgroups. As a result, the beneficiaries were chosen by a proportionate random sample technique and were examined from among five major courses. When the total results were evaluated, regardless of the course group, it was discovered that the beneficiaries’ caste classification, land ownership, exposure to the media, and cosmopoliteness had a substantial correlation with their level of knowledge. The stepwise regression study indicated that caste category and cosmopoliteness had a significant impact on knowledge growth in variance terms. Beneficiaries of several group areas with the lowest knowledge level in the case of medical & nursing courses were shown to have significant variations in knowledge.